Collins primary literacy:pupil book 2 - Law, Karina (Harpercollins Publishers London, 2008)
Collins Primary Literacy Pupil Book 2 features fiction from Jill Murphy and Francesca Simon, poetry from Michael Rosen, and exciting non-fiction on snakes and birds. Pupil Book 2 covers a wide variety of text types and topics, and provides engaging activities to help you deliver the objectives of the renewed Framework.